Systematics of Robustagramma, a new genus of New World Sphaeroceridae (Diptera) - Marshall, Stephen A.; Cui, Yongsheng (Zootaxa, 2005)
The genus Robustagramma is described for a distinctive clade of Limosininae occurring from Canada south to Argentina. Keys, descriptions, distributional data and phylogenetic hypotheses are provided for 8 species groups and 54 species. Fifty-two of the 54 included species are described as new.